ANALISIS SISTEM PENGENDALIAN INTERN TERHADAP PENJUALAN DI SPBU 24.332.124 AIR KENANGA - Vianti, Angelina; Novika; Tri Setyo Mulyani , Hendarti (Jurnal Akuntansi Bisnis Dan Keuangan, 2024)
This research aims to determine the internal control system over sales at SPBU 24.332.124 Air Kenanga. The techniques used in data collection were interviews, documentation, and literature study. The data analysis technique used was descriptive qualitative. The results showed that the internal control system over sales at SPBU 24.332.124 Air Kenanga with the theoretical component internal control system according to the expert based on COSO theory was not fully in accordance. In the Control Activity, there were still duplication of duties for the Security Guard that is concurrently the task of calculating revenue from daily sales and managing sales of 3 kg LPG gas. Moreover, SPBU 24.332.124 Air Kenanga does not backup data on computers in the office. In the Control Environment which includes integrity and ethical values, commitment to competence, audit committee and board of directors, management philosophy and operating style, organizational structure, determination of authority and responsibility, policies and human resources are good and appropriate. Risk Assessment, Information and Communication, and Monitoring are good and appropriate.